How Young Italians Negotiate and Redefine Their Identity in the Mobility Experience - Mauro Giardiello; Hernan I. Cuervo; Rosa Capobianco (Societies, 2024)
In this article we analyze the formation of different identity models of Italian young people experiencing mobility. The article contributes to study the link between youth mobility and identity. It does so through the development of a theoretical perspective that combines Butler’s post-structuralism with Bourdieu’s category of embodied cultural capital. Drawing on this theoretical framework, we analyze the identity formation of young Italians who emigrated to Australia in the last 10 years. The data show the emergence of an identity made up of a complex set of interconnected levels, composed of an incorporated dimension that constitutes the basis of their roots and the performative part that represents the mobile dimension subject to transformation in the course of life evolution. This interpretative lens enables the understanding of how the process of incorporation is connected to the performative and self-transformative one of identity, but also how the different combination of fixed and mobile aspects defines different profiles of identity and a different way of perceiving being Italians.